2009
DOI: 10.3109/13561820903078249
|View full text |Cite
|
Sign up to set email alerts
|

Wound care in primary health care: District nurses' needs for co-operation and well-functioning organization

Abstract: Most patients with leg- and foot ulcers are managed within non-institutional care. The aim of this study was to investigate the district nurses' wound management, including wound appearance, assignment of responsibility, guidelines for wound treatment and co-operation with other professional groups. The study has a descriptive quantitative approach. Data was collected using a wound registration form and a questionnaire. The selection of participants was made by random sampling. District nurses (n = 26) in five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 16 publications
0
32
0
2
Order By: Relevance
“…The study identified challenging collaboration with GPs as an important aspect of complex treatment. Previous studies have found that barriers to following guidelines include lack of routines for cooperation between nurses and GPs (Eskilsson & Carlsson, 2010; Friman et al, 2010) and/or GPs’ lack of access to clinical guidelines and experience treating chronic leg ulcers (Cullen & Phillips, 2009; Graham, Harrison, Shafey, & Keast, 2003). DNs’ strategies for avoiding consequences of this obstacle included proactively informing GPs when it was time to take action, such as when a patient needed a referral to a dermatology clinic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study identified challenging collaboration with GPs as an important aspect of complex treatment. Previous studies have found that barriers to following guidelines include lack of routines for cooperation between nurses and GPs (Eskilsson & Carlsson, 2010; Friman et al, 2010) and/or GPs’ lack of access to clinical guidelines and experience treating chronic leg ulcers (Cullen & Phillips, 2009; Graham, Harrison, Shafey, & Keast, 2003). DNs’ strategies for avoiding consequences of this obstacle included proactively informing GPs when it was time to take action, such as when a patient needed a referral to a dermatology clinic.…”
Section: Discussionmentioning
confidence: 99%
“…They share the responsibility for patient care with other professionals, such as GPs, registered nurses, assistant nurses and medical social workers (Lagerin et al, 2007; Strandberg, Ovhed, Borgquist, & Wilhelmsson, 2007). DNs often treat patients with leg ulcers, both at health care centres and in home care (Friman, Klang, & Ebbeskog, 2010). Since healing is often slow and recurrence rates are high, treatment requires a great deal of nursing time and a large amount of dressing materials (Öien & Forssell, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Sweden showed nurses' experiences in the treatment of wounds in the context of PHC and emphasize the challenges of providing care for these lesions, considering the complicating factors that overlap with this care (6)(7) .…”
Section: Descriptorsmentioning
confidence: 99%
“…Another study, 10 illustrated the importance of IPC in the treatment of wounds. The authors found that IPC can potentially reduce prevalence of wounds and improve wound care more efficiently.…”
Section: Introductionmentioning
confidence: 99%